IMPLEMENTASI KEBIJAKAN SMART CITY DALAM PENGELOLAAN SAMPAH DI KOTA MAKASSAR - Nasir, Nasir (Jurnal Dialektika Politik, 2025)
The increase in population and economic activity in Makassar City has caused a significant surge in waste volume. The Makassar City Government implements the Smart City policy in waste management to increase the efficiency and effectiveness of the waste system. This study aims to analyze the implementation of Smart City policies in waste management and identify the challenges faced in its implementation. The research method used is a descriptive qualitative approach, with data collection techniques through in-depth interviews, observations, and documentation studies. The research informants consisted of officials of the Makassar City Environmental Agency, waste management business actors, and people who use technology-based waste services. The results of the study show that the Smart City policy in waste management has been implemented through several innovations, such as the use of the Makassar Not Rantasa (MTR) application for hygiene monitoring, a digital waste bank system, and the optimization of GPS tracking-based transport fleets. However, the implementation of this policy still faces challenges, including low technological literacy among the public, limited digital infrastructure, and suboptimal coordination between institutions. The contribution of this research lies in the identification of factors that support and hinder the successful implementation of Smart City in waste management. This finding is expected to be a reference for local governments in designing more inclusive and sustainable technology-based policies to improve environmental governance in urban areas.